(untitled) - Régnier, Emilie; Hubau, Agathe; Touzé, Solène; Guignot, Sylvain; Meyer, Daniel; Diat, Olivier; Bourgeois, Damien (Comptes Rendus. Chimie, 2024)
Aqueous foams have been used in various hydrometallurgical processes, and have recently emerged as an alternative technique for the leaching of metallic copper, using hydrochloric acid and O2 from air as an oxidant. In the present study, we describe how this technique has been successfully applied to the leaching of copper from waste printed circuits boards (WPCBs). First of all, the use of HCl based foams was successfully applied to the leaching of sole copper, and the impact of the size of copper particles was studied. It was demonstrated that use of mixtures of fine and large particles give excellent results. Then, on ground WPCBs, a first classical leaching stage using aqueous HCl solution was performed in order to remove maximum quantity of reducible metals (aluminum, iron, zinc ...). Then, almost quantitative copper leaching employing HCl based foam was performed. Copper is almost exclusively leached during this stage, and the complete mass balance in 5 major metals present in WPCBs (aluminum, iron, zinc, nickel and copper) is detailed. Kinetics of the copper leaching were greatly enhanced through addition of substoechiometric quantity of cupric ions at the beginning of the process, so that extensive grinding of the waste is not necessary.